Team Reasoning, Framing, and Self-Control: An Aristotelian Account - Gold, N (Oxford University Press, 2014)
Decision theory explains weakness of will as the result of a conflict of incentives between different transient agents. In this framework, self-control can only be achieved by the I-now altering the incentives or choice-sets of future selves. There is no role for an extended agency over time. However, it is possible to extend game theory to allow multiple levels of agency. At the inter-personal level, theories of team reasoning allow teams to be agents, as well as individuals. I apply team reasoning at the intra-personal level, taking the self as a team of transient agents over time. This allows agents to ask, not just “what should I-now do?’, but also ‘What should I, the person over time do?’, which may enable agents to achieve self-control. The resulting account is Aristotelian in flavour, as it involves reasoning schemata and perception, and it is compatible with some of the psychological findings about self-control.